A STUDY OF THE EFFECT OF DIFFERENT EXTRACT OF MEDICINAL PLANTS ON HUMAN HEALTH - RANJAN PRABHAKAR (International Journal of Multidisciplinary Research and Studies, 2020)
In the past thirty years, there has been a significant rise in the number of people using herbal supplements and treatments. The use of herbal medicine as a treatment for a variety of ailments has shown both promising and beneficial possibilities. Herbal and phytoconstituent medicines are gaining popularity all over the world, and an increasing number of individuals are turning to herbal treatments as a means of treating a variety of health conditions. The emergence of antimicrobial resistance as a result of the irresponsible use of antibiotics presents a challenge for human civilization on a scale that has never been seen before. Infections caused by bacteria are notoriously difficult to treat because of the tendency of germs to develop resistance to a diverse array of antimicrobial medications. The potential antibacterial activity of new compounds is being investigated and measured in an effort to find substances with few or no adverse effects. Researchers from all around the world are looking at the wide variety of medicinal plants that are referred to in Unani, Ayurveda, and Siddha. PubMed, Research Gate, Science Direct, and Google Scholar are examples of well-known and widely acclaimed global databases that were searched with a variety of search strings. Indian medicinal plants, multidrug resistance (MDR), thin layer chromatography (TLC), antimicrobials, and synergism were used in a variety of combinations to reclaim numerous citations associated with this field. As a result, the purpose of this study is to throw some light on the knowledge of medicinal plants as a possible basis for herbal medications and to illustrate how synergism and TLC bioautography play a significant part in the process of discovering antimicrobial chemicals.